Distinctive Personality Traits of Couch Basketball Players - A Field Study of the Noor Al-Maseela Couch Basketball Team Players - Cherifi, halim; hbora, Mohammed (sports creativity, 2025)
Today, sports are witnessing significant development and occupy a prominent place in the cultural calendar of various nations, encompassing all segments of society and different age groups, including people with disabilities. National and regional athletes from various countries with disabilities have achieved remarkable and advanced results in various sports activities. Examples of this include the achievements in the recent Paralympic Games in Atlanta and Sydney (1996 and 2000). According to the scientific approach to sports training, which aims to help them reach high athletic levels, it is essential to utilize all physical, technical, tactical, and psychological capabilities in an integrated manner to achieve high-level athletic performance and break records. The psychological aspect is considered one of the important pillars that should not be neglected in training people with disabilities, and many scientific studies and research in the field of sports have proven its role in achieving high athletic achievement. Personality is a crucial element in psychological preparation programs for people with disabilities. Muhammad Hassan Abu Abiya (1986) states that each sporting activity has specific requirements for developing an athlete's personality, and sports activities as a whole have distinctive characteristics. To succeed in a particular sport, certain personality traits must be present. An athlete lacking positive psychological traits will not be able to achieve the highest levels, regardless of their physical and technical abilities, because these traits directly influence personality development (21-175). In the early stages of athlete preparation, integration is essential, focusing on developing physical and technical skills alongside personality aspects, including personality traits. This ensures that the positive impact of these traits is maximized in the competitive arena and that they are not neglected, lest they hinder the achievement of high-level performance. As previously mentioned, the nature of high-level sports requires athletes to utilize their physical, technical, tactical, and psychological abilities to the fullest extent possible in order to achieve their best performance. This involves integrating personality traits, which represent a crucial dimension in the psychological preparation of athletes. These traits play a significant role in performance development and are now considered one of the psychological variables that must be addressed alongside physical, technical, and tactical requirements. Wheelchair basketball – a sport for athletes with physical disabilities – is a competitive activity characterized by dynamic movement that demands rapid response to the demands of the game. It is also characterized by direct competition between players and is replete with intense and rapidly changing psychological pressures that can affect a player's technical and tactical performance, and consequently, the outcome of the game. Therefore, it is essential for coaches to plan early on to develop the personality traits of wheelchair athletes, which directly impact their athletic performance, enabling them to achieve victory in competitions alongside their physical, technical, and tactical preparation. From this perspective, the researcher embarked on this study, which aims to identify the distinctive personality traits of wheelchair athletes. This could contribute to utilizing these traits in psychological preparation programs for wheelchair athletes, developing their personality traits that directly influence their athletic performance and enhance their achievement motivation, which is linked to competitive athletic situations and positively impacts their performance and match results.